A multicenter, randomized, double-blind dose-ranging study of glycopyrrolate/formoterol fumarate fixed-dose combination metered dose inhaler compared to the monocomponents and open-label tiotropium dry powder inhaler in patients with moderate-to-severe COPD. (November 2016) - Tashkin, Donald P.; Martinez, Fernando J.; Rodriguez-Roisin, Roberto; Fogarty, Charles; Gotfried, Mark; Denenberg, Michael; Gottschlich, Gregory; Donohue, James F.; Orevillo, Chad; Darken, Patrick; St Rose, Earl; Strom, Shannon; et al.
Abstract: Background: This study formed part of the dose selection for a glycopyrrolate (GP)/formoterol fumarate (FF) fixed-dose combination formulated using novel Co-Suspension™ Delivery Technology and delivered via a metered dose inhaler (GFF MDI). The study aimed to confirm the optimal dose of GP to formulate with FF 9.6 μg in the fixed-dose combination product, GFF MDI. Methods: This multicenter, randomized, double-blind, chronic-dosing, balanced incomplete block, crossover study (NCT01587079) compared five doses of GFF MDI (18/9.6, 9/9.6, 4.6/9.6, 2.4/9.6 and 1.2/9.6 μg, twice daily [BID]) with its monocomponents FF MDI 9.6 μg and GP MDI 18 μg (both BID) and open-label tiotropium (18 μg once daily) as the active control. The primary efficacy endpoint was change from baseline in forced expiratory volume in 1 s area under the curve from 0 to 12 h (FEV1 AUC0–12 ) on Day 7. Results: In total, 159 patients were randomized to treatment and 132 patients (52.2% male, mean age 62.8 years) were included in the intent-to-treat population. All doses of GFF MDI (except 1.2/9.6 μg) resulted in statistically significant improvements in FEV1 AUC0–12 versus monocomponents and open-label tiotropium. GFF MDI 18/9.6 μg consistently showing the greatest improvement over monocomponents and open-label tiotropium. Adverse events for each GFF MDI dose were similar versus GP MDI 18 μg, FF MDI 9.6 μg and open-label tiotropium. Conclusions: These findings further support selection of GP 18 μg as the optimal dose to combine with FF MDI 9.6 μg for advancement into Phase III clinical trials of GFF MDI. Highlights: Of the dose-range evaluated, GFF MDI 18/9.6 μg was the most effective at improving lung function. GFF MDI 18/9.6 μg significantly improved FEV1 AUC0−12 vs GP MDI 18 μg, FF MDI 9.6 μg and open-label tiotropium. All doses of GFF MDI (except 1.2/9.6 μg) significantly improved FEV1 AUC0–12 vs comparators, in a dose-ordered manner. Adverse event profiles were similar across all treatment groups. GP 18 μg was determined as the optimal dose to combine with FF MDI 9.6 μg for Phase III trials.